2005
DOI: 10.1002/ajmg.a.30812
|View full text |Cite
|
Sign up to set email alerts
|

Cystathionine beta-synthase c.844ins68 gene variant and non-syndromic cleft lip and palate

Abstract: Non-syndromic cleft lip with or without cleft palate (CL/P) is a common birth defect with substantial clinical and social impact and whose causes include both genetic and environmental factors. Folate and homocysteine (Hcy) metabolism have been indicated to play a role in the etiology of CL/P, and polymorphisms in folate and Hcy genes may act as susceptibility factors. We investigated a common polymorphism in the cystathionine beta-synthase (CBS) gene (c.844ins68) in 134 Italian CL/P cases and their parents us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
2

Year Published

2005
2005
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 41 publications
(39 reference statements)
4
33
2
Order By: Relevance
“…3A). These results were modest and not concordant with a previous study of this gene in clefts [Rubini et al, 2005]. CBS performs the rate-limiting step in the transsulfuration pathway that degrades homocysteine [Finkelstein, 1990], and this SNP was associated with a decrease in the total homocysteine/cystathionine ratio [Fredriksen et al, 2007].…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…3A). These results were modest and not concordant with a previous study of this gene in clefts [Rubini et al, 2005]. CBS performs the rate-limiting step in the transsulfuration pathway that degrades homocysteine [Finkelstein, 1990], and this SNP was associated with a decrease in the total homocysteine/cystathionine ratio [Fredriksen et al, 2007].…”
Section: Discussioncontrasting
confidence: 91%
“…k Zhu et al [2005]. l Rubini et al [2005]. have suggested protection from CL/P by the MTHFR T allele in mothers [van Rooij et al, 2003;Gaspar et al, 2004;Nurk et al, 2004] and children [Shaw et al, 1998;Grunert et al, 2002;Shotelersuk et al, 2003;Gaspar et al, 2004], although none reached statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, because parent-of-origin effects have been previously described for oral-cleft candidate genes (Scapoli et al 2002;Rubini et al 2005), we tested TGFB3 variants for evidence of genomic imprinting. Interestingly, however, we found evidence of a lower risk of maternal transmission compared with paternal transmission (I M = 0.38; CI: 0.17-0.86) of allele T to the affected offspring at marker rs2300607 (IVS1 +5321) (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…As this is the most convincing human study of TGFB3 in CL/P published to date, we investigated the relevance of their findings for CL/P patients of a different ethnic background, namely, patients of central European origin. In addition, we searched for parent-of-origin effects, which have been previously described for candidate genes associated with nonsyndromic oral clefts (Scapoli et al 2002;Rubini et al 2005). …”
Section: Introductionmentioning
confidence: 99%
“…For example, functional RFC1 and MTHFR variants in probands revealed no association with CL/P in a South American population [62]. However, a log-linear-based method revealed a geneenvironment interaction between CP infants carrying either CT or TT genotypes at MTHFR and maternal folic acid consumption [63] and another study found similar findings for CL/P [64]. Also, an increased risk has been observed for maternal MTHFR variants [65,66].…”
Section: Genes In Environmental Pathwaysmentioning
confidence: 99%